Drivers of Subseasonal Forecast Errors of the East African Short Rains. Issue 14 (22nd July 2021) - Kolstad, E. W.; MacLeod, D.; Demissie, T. D.
Abstract: The 'short rains' in East Africa from October to December have significant year‐to‐year variability. Their abundance or deficiency is often associated with floods or droughts for which early warning is crucial, though even in normal seasons skillful forecasts facilitate planning and preparedness. Here we study the relationship between initial‐state sea surface temperatures and subseasonal rainfall forecast errors in the European Center for Medium‐Range Weather Forecasts model in the region. We demonstrate that the initial mode of the Indian Ocean Dipole (IOD) is a partial control on the rainfall error in weeks 3–4. This relationship is also clear on the seasonal scale, exemplified by too‐wet forecasts during the 2015 season when the IOD was positive, and too‐dry forecasts in 2010 when it was negative. Our results provide an entry point for model improvement, and we show that a priori forecast corrections based on the initial IOD index are feasible. Plain Language Summary: In East Africa, the rainfall is usually concentrated in specific periods of the year. One of these periods occurs between October and December and is called the 'short rains'. Failure of the short rains can have disastrous effects on farmers and pastoralists, as there exist little infrastructure for irrigation in the region. Similarly, too heavy rains can yield devastating floods. Advance knowledge of the timing and nature of the short rains is therefore crucial for planning and preparedness. However, the usefulness of any prior information is contingent on accurate forecasts, which are mainly based on numerical models. Here we study the ability of a widely used such model, focusing on whether it is possible to predict the model error already when the forecasts are issued. We find that the sea surface temperatures in the nearby Indian Ocean influence the development of rainfall errors in the model. This information can be used to guide upfront forecast correction, but it also offers a diagnosis that can inform model improvements. Both actions have the potential to enhance the quality of East African rainfall forecasts. Key Points: Subseasonal forecast errors of the East African 'short rains' at 3–4 weeks' lead time are studied for the European Center for Medium‐Range Weather Forecasts monthly forecasting system The rainfall errors are linked to the initial state of the Indian Ocean dipole through forecast errors of oceanic and atmospheric drivers Knowledge about these conditional errors can be used for a priori forecast correction and to inform targeted model improvements